Hospital bronchoscopy-related pseudo-outbreak caused by a circulating Mycobacterium abscessus subsp. massiliense. Issue 3 (November 2018) - Fernandes Garcia de Carvalho, N.; Rodrigues Mestrinari, A.C.; Brandão, A.; Souza Jorge, L.; Franco, C.; da Silveira Paro Pedro, H.; de Lucca Oliveira, M.G.; Blaz Trombim, P.E.; Brandão, D.; Ferrazoli, L.; Chimara, E.
Summary: Adolfo Lutz Institute in Sao Paolo State performs mycobacterial identification for many healthcare units, and in 2008 identified a possible outbreak involving patients submitted to bronchoscopy at the same hospital. This study aimed to analyse the clonality of isolates. Mycobacterium abscessus subsp. massiliense isolated from 28 patients, water from one bronchoscope and water from four automated endoscope reprocessing machines presented high similarity by pulsed-field gel electrophoresis. This strain was not found in the water supply, and it was hypothesized that an infected patient contaminated the bronchoscope, with further false-positive cultures from subsequent patients.